2014
DOI: 10.1080/00103624.2014.932368
|View full text |Cite
|
Sign up to set email alerts
|

Rates of Nitrogen Mineralization of Meat and Bone Meals in Mediterranean Soils

Abstract: Animal by-products such as meat and bone meals are now certified as free from bovine spongiform encephalopathy (BSE), and their use as organic fertilizers is considered safe again. Given that knowing the rates at which their nutrients are released is key to efficient use, nitrogen (N) mineralization in Mediterranean soils fertilized with meat and bone meals (MBMs) has been studied by means of 12 incubation experiments using three soils of different textures and organic-matter contents and five MBMs of varied o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…Measurements of leaf chlorophyll content at both locations revealed that the corn plants subjected to rates of 224 kg N ha −1 and below did not reach their full yield potential as compared to the well-fertilized rates. This validated the previous work on MBM mineralization that showed ~75% of N was released within 90 days [18,19] where 75% of the amount of N applied from MBM will be mineralized and available for plant uptake. Application rates lower than 224 kg N ha −1 did not supply the sweet corn with sufficient N for optimum growth and yield.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Measurements of leaf chlorophyll content at both locations revealed that the corn plants subjected to rates of 224 kg N ha −1 and below did not reach their full yield potential as compared to the well-fertilized rates. This validated the previous work on MBM mineralization that showed ~75% of N was released within 90 days [18,19] where 75% of the amount of N applied from MBM will be mineralized and available for plant uptake. Application rates lower than 224 kg N ha −1 did not supply the sweet corn with sufficient N for optimum growth and yield.…”
Section: Discussionsupporting
confidence: 88%
“…For MBM mineralization, Ahmad et al [18] found the N release to be 20% in the first 14 days and up to 75% within 90 days, in a leachate column with two Hawai'ian soils. Similarly, Chaves et al [19] reported 18% to 37% of the N was released in the first 14 days after soil application in Spain.…”
Section: Introductionmentioning
confidence: 79%
“…In the current study, HLA soil was characterized by a higher content of C organic and N total as well as lower specific density and bulk density, which could have contributed to higher maize grain yields than in HLL soil. According to Chaves et al [78], the rate of MBM mineralization is determined mainly by soil type. Meat and bone meal is mineralized more rapidly in loamy soil, which can be attributed not only to the physical but also to the biological and chemical properties of soil.…”
Section: Discussionmentioning
confidence: 99%
“…The provision of optimum conditions for nitrogen nutrition using exclusively organic fertilisers is complex because mineralisation enhanced the yield of grain as compared with the 1.0 t ha −1 MBM, and no fertilisation treatments coincide with the dynamics of nitrogen uptake by crops [32]. Therefore, when considering fertilisation with organic fertilisers, including MBM, not only the direct effect but also the consequent effect needs to be taken into account [4,8,[33][34][35][36].…”
Section: Discussionmentioning
confidence: 99%